Report highlights: Misinformation across social media platforms and across countries - Boulianne, Shelley; Belland, Stephanie; Tenove, Chris; Friesen, Kelsey (My University, 2021)
This infographic highlights key findings from a four-country (USA, UK, France, Canada) survey conducted in February 2021.
Keywords: misinformation; social media